The impact of PISA on Brazilian publications indexing in the portal of periodicals of CAPES (Research, Society and Development, 2018)
This research aims to analyze the papers whose mention PISA and approach the brazilian context, and how the brazilian papers has been influenced by the PISA. To this, we develop a state of art research, with the terms PISA and OECD on the 'CAPES Portal of Papers'. We selected only papers in Portuguese, resulting in 28 publications. The results show how just recently the brazilian researches has approach the PISA, the first production is dated by 2006. Recently we have a significant increase in the productions about PISA, mainly because the increase in the mathematics teaching publications about the theme. The PISA has a great impact in the educational public policies and in the research in worldwide, and this tendency is coming now to the brazilian context. The results suggest that the constant increase of productions in Brazil about PISA, has influenced by the performance of the students in this assessment in the attempt to increase this performance.